2013
DOI: 10.3390/md11030800
|View full text |Cite
|
Sign up to set email alerts
|

Helicusin E, Isochromophilone X and Isochromophilone XI: New Chloroazaphilones Produced by the Fungus Bartalinia robillardoides Strain LF550

Abstract: Microbial studies of the Mediterranean sponge Tethya aurantium led to the isolation of the fungus Bartalinia robillardoides strain LF550. The strain produced a number of secondary metabolites belonging to the chloroazaphilones. This is the first report on the isolation of chloroazaphilones of a fungal strain belonging to the genus Bartalinia. Besides some known compounds (helicusin A (1) and deacetylsclerotiorin (2)), three new chloroazaphilones (helicusin E (3); isochromophilone X (4) and isochromophilone XI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 36 publications
(51 reference statements)
0
31
0
Order By: Relevance
“…Albeit an IC 50 for enzyme or receptor inhibition is provided, no mechanism of action studies were reported at the time of publication: alotaketal C ( 224 ) [215]; aspergentisyl A ( 225 ) [216]; A. terreus butyrolactone ( 226 ) [217]; caulerpine ( 227 ) [218]; conicasterol F ( 228 ) [219]; D. avara sesquiterpene ( 229 ) [220]; D. gigantea sterols ( 230 , 231 ) [221]; dysidavarone A ( 232 ) [222]; galvaquinone B ( 233 ) [223]; halicloic acids A and B ( 234 , 235 ) [224]; isochromophilone XI ( 236 ) [225]; leucettamols A and B ( 237 , 238 ) [226]; manadosterol A ( 239 ) [227]; marilines A1 and A2 ( 240 , 241 ) [228]; methyl sarcotroate B ( 242 ) [229]; P. citrinum sorbicillinoid ( 243 ) [230]; phosphoiodyn A ( 244 ) [231]; purpuroines A and D ( 245 , 246 ) [232]; santacruzamate A ( 247 ) [233]; sarcophytonolide N ( 248 ) [234]; sargassumol ( 249 ) [235]; sesquibastadin 1 ( 250 ) [236]; S. glaucum cembranoids ( 251 – 253 ) [237]; symplocin A ( 254 ) [238]; tsitsikammamine A derivative ( 255 ) [239]; V. lanosa bromophenol ( 256 ) [240] ; and X. testudinaria fatty acid ( 257 ) [241]. …”
Section: Marine Compounds With Miscellaneous Mechanisms Of Actionmentioning
confidence: 99%
“…Albeit an IC 50 for enzyme or receptor inhibition is provided, no mechanism of action studies were reported at the time of publication: alotaketal C ( 224 ) [215]; aspergentisyl A ( 225 ) [216]; A. terreus butyrolactone ( 226 ) [217]; caulerpine ( 227 ) [218]; conicasterol F ( 228 ) [219]; D. avara sesquiterpene ( 229 ) [220]; D. gigantea sterols ( 230 , 231 ) [221]; dysidavarone A ( 232 ) [222]; galvaquinone B ( 233 ) [223]; halicloic acids A and B ( 234 , 235 ) [224]; isochromophilone XI ( 236 ) [225]; leucettamols A and B ( 237 , 238 ) [226]; manadosterol A ( 239 ) [227]; marilines A1 and A2 ( 240 , 241 ) [228]; methyl sarcotroate B ( 242 ) [229]; P. citrinum sorbicillinoid ( 243 ) [230]; phosphoiodyn A ( 244 ) [231]; purpuroines A and D ( 245 , 246 ) [232]; santacruzamate A ( 247 ) [233]; sarcophytonolide N ( 248 ) [234]; sargassumol ( 249 ) [235]; sesquibastadin 1 ( 250 ) [236]; S. glaucum cembranoids ( 251 – 253 ) [237]; symplocin A ( 254 ) [238]; tsitsikammamine A derivative ( 255 ) [239]; V. lanosa bromophenol ( 256 ) [240] ; and X. testudinaria fatty acid ( 257 ) [241]. …”
Section: Marine Compounds With Miscellaneous Mechanisms Of Actionmentioning
confidence: 99%
“…The bioassays with the clinically relevant bacterial strains Staphylococcus epidermidis (DSM 20044), methicillin-resistant Staphylococcus aureus (MRSA) (DSM 18827), and the causative agent of acne, Propionibacterium acnes (DSM 1897 T ), were performed as described by Silber et al [32]. The phytopathogenic fungus Septoria tritici and the dermatophytic fungus Trichophyton rubrum as well as the cytotoxic effect on the human hepatocellular liver carcinoma cell line HepG2 were tested according to Jansen et al [33]. Inhibition of the enzymes glycogen synthase kinase (GSK-3β), acetylcholinesterase (AchE), phosphodiesterase (PDE-4B2), and protein tyrosine phosphatase (PTP1B) was determined according to Baki et al [34], Ohlendorf et al [31], Schulz et al [35], and Silber et al [36], respectively.…”
Section: Methodsmentioning
confidence: 99%
“…co-cultured with Bacillus subtilis 41 Peniazaphilin A (77) Penicillium sp. CPCC 400786 13 Antiviral (HIV: 60.4 mM) Monapilosusazaphilone (78) Monascus pilosus 103 Monascusazaphilone A (79) Monascus purpureus BCRC 38108 43 Anti-inammatory (inhibit NO production: 4.6 mg mL À1 ); cytotoxic (LPS-induced RAW264.7: cell viability 83%) Monascusazaphilone B (80) Monascus purpureus BCRC 38108 43 Anti-inammatory (inhibit NO production: 8.88 mg mL À1 ); cytotoxic (LPS-induced RAW264.7: cell viability 85%) Berkchaetoazaphilone C (81) Pleurostomophora sp. 49…”
Section: -Epi-pestafolide a (76)mentioning
confidence: 99%
“…77 The fungus Bartalinia robillardoides strain LF550, obtained from the Mediterranean sponge Tethya aurantium, metabolized two novel chloroazaphilones, helicusin E (175) and isochromophilone XI (176). 78 Inducing the Mediterranian sponge Agelas oroides derived fungus Penicillium canescens by using 5% NaBr, resulted in two new brominated azaphilones, bromophilones A and B (177-178). Notably, 178 showed moderate cytotoxicity against the mouse lymphoma cell line L5178Y and the human ovarian cancer cell line A2780 with IC 50 values of 8.9 and 2.7 mM, respectively, while 177 was less active.…”
Section: Sclerotiorin-like Azaphilonesmentioning
confidence: 99%
See 1 more Smart Citation